Inter-daily temperature variability in the southern Rocky Mountains of Colorado - Steen, Brian, author; Fassnacht, Steven, advisor; Barnard, David, committee member; Ronayne, Michael, committee member (Colorado State University. Libraries, 2024)
While daily temperature variability has decreased in northern latitudes, variability across the western United States has increased. Changes in temperature variability can influence hydrological and earth system processes that could have severe ecological impacts. Mountainous areas are more sensitive to warming trends, but daily temperature variability in the Rocky Mountains is unknown. We investigated daily temperature trends across the Yampa and Rio Grande watersheds of the Southern Rocky Mountains in Colorado using 23 Snow Telemetry (SNOTEL) stations at high elevation, snow-covered regions (2521-3536m) and ten Cooperative Observer Program (COOP) stations at lower elevations (1961-2840m). SNOTEL data were homogenized to account for temperature sensor changes in 2003-2006, with five possible bias correction combinations compared. Daily data were detrended using the long-term and annual means, so that the day-to-day variability could be quantified. Trends were analyzed from the mid-1980s to 2022 using the Mann‐Kendall significance test and Theil‐Sen's rate of change. Inter-daily temperature variability (ITV) changed over the 30+ year period of evaluation with mixed increases and decreases based on location and time period. Variability in the spring at 26 stations has increased upwards of 0.8°C per 30 years in the spring. Ninety percent of stations have increased in variability up to 1.0°C per 30 years in the fall. In the summer, Yampa area stations decreased in variability while the Rio Grande area stations increased, both significantly. Low elevation COOP stations demonstrated smaller increases in variability than high elevation SNOTEL stations in the Rio Grande watershed throughout all seasons. The Yampa watershed showed no similar elevational patterns, but rather decreased variability for SNOTEL stations with little change for variability for COOP stations. The scattered decreases in the Yampa area and at lower elevations emphasize the spatiotemporal variability of montane climatology and suggest increased ITV trends across the Rocky Mountain West are watershed and station specific.